Thermal Conductivity Study of Geopolymer Material as a Heat Insulating Material for Thermal Storage - KHOSHAIMI, NUR ATHIRAH WAHIDA; Prof. Ts. Dr. Zaidi Bin Embong ,; Ahmad Hassan Sallehudin, (Enhanced Knowledge in Sciences and Technology, 2024)
Thermal building insulation is one of the most crucial factors in obtaining perfect thermal storage architecture and becoming the best thermal storage. The primary goals of this study were to explore the materials used in thermal storage structures composed of geopolymer material in a way of identifying its elemental composition, measuring its density, as well as to analyze its thermal properties, particularly its thermal conductivities. There were two parameters in this study which are the type of raw samples and the weight of sample mixtures. Firstly, the pellets' diameter and thickness were measured first after the sample was turned into pallet form. Then, the SEM-EDX analysis was used to examine the sample's characteristics and the morphology of the sample was determined. Later the density of the sample was measured as it influences the sample’s ability to conduct heat. For the density measurement, the 2g mixture sample has the lowest density at 0.001752 Kg/m³. Raw limestone has the highest density at 0.001826 Kg/m³, followed by coconut peat ash and kaolin. Finally, the thermal conductivity occurred for each sample using data obtained. Based on the analysis, 6g sample mixture has the lowest thermal conductivity of 1.3117 (W/m℃), while for raw samples, kaolin is the lowest thermal conductivity with avalue of 1.4320 (W/m℃).